The Effect of Digitalization on Energy Trilemma in the MENA region - Abdallah , Manar M.; Helmy , Omneia; Ibrahiem , Dalia M. (Journal of Ecohumanism, 2025)
The Middle East and North Africa (MENA) region faces numerous challenges while ensuring energy security, affordability, and environmental sustainability. A wide range of studies suggest that digitalization, alongside efficient energy conversion technologies, can help address the three conflicting energy trilemma dimensions (i.e., energy security, affordability, and environmental sustainability) (Salah et al., 2022). The study will investigate the effect of digitalization on the energy trilemma dimensions individually and collectively by creating an energy trilemma index using the Principal component analysis (PCA). The study employed the generalized method of moment (GMM) for 11 MENA countries over the period 2000–2021 to investigate the effect of digitalization on the energy trilemma and its dimensions in the short run while employing the fully modified ordinary least squares (FMOLS) to investigate the same effect in the long run. The GMM results reveal that digitalization has an insignificant effect on the energy trilemma index and its three dimensions in the short run. The FMOLS results reveal a positive effect of digitalization on the energy trilemma index and its energy security and affordability dimensions while a negative effect on the environmental sustainability dimension in the long run. These findings emphasize the paramount importance of digitalization in improving energy trilemma dimensions.